Introduction to "The Politics of Educational Reforms". Issue 2 (2nd April 2016) - Apple, Michael W.
Abstract: It has become increasingly clear that education is a site of conflict. This essay examines the ideological positions that now dominate educational reforms and suggests a number of roles that critically democratic educators should play in -confronting these reforms. It then details the contributions that the authors -included in this special issue make toward understanding both the limits of current reforms and the possibilities of interrupting them.